2023
DOI: 10.1002/ijc.34488
|View full text |Cite
|
Sign up to set email alerts
|

Trends in best‐case, typical and worst‐case survival scenarios of patients with non‐metastatic esophagogastric cancer between 2006 and 2020: A population‐based study

Abstract: New treatment options and centralization of surgery have improved survival for patients with non-metastatic esophageal or gastric cancer. It is unknown, however, which patients benefitted the most from treatment advances. The aim of this study was to identify best-case, typical and worst-case scenarios in terms of survival time, and to assess if survival associated with these scenarios changed over time. Patients with non-metastatic potentially resectable esophageal or gastric cancer diagnosed between 2006 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Since such a study design has not been used before in patients with pancreatic cancer, it was difficult to predict to what extent the use of systemic chemotherapy and other best practices could be improved. Importantly, for other cancers with poor survival, such as esophageal and gastric cancer, it has also been shown that improvements in survival are mainly observed in selected best-case patients, while improvement of survival for the population as a whole is not observed . Moreover, the Netherlands is a small country, even though significant variability in practice is present, this is potentially less variable compared with other (larger) countries.…”
Section: Discussionmentioning
confidence: 99%
“…Since such a study design has not been used before in patients with pancreatic cancer, it was difficult to predict to what extent the use of systemic chemotherapy and other best practices could be improved. Importantly, for other cancers with poor survival, such as esophageal and gastric cancer, it has also been shown that improvements in survival are mainly observed in selected best-case patients, while improvement of survival for the population as a whole is not observed . Moreover, the Netherlands is a small country, even though significant variability in practice is present, this is potentially less variable compared with other (larger) countries.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment and survival of patients with gastric or gastro-esophageal junctional (GEJ) carcinoma have shown progress over the last decades. The introduction of perioperative chemotherapy for resectable disease and centralization of gastric surgery have improved patients' prognosis as shown in clinical trials [1,2]. Despite these improvements, 5-year survival rate for potentially curable gastric cancer patients in the Netherlands has only seen a minor increase from 27% during 2000-2010 to 34% in 2011-2020 [3].…”
Section: Introductionmentioning
confidence: 99%